Społeczna odpowiedzialność biznesu a środowiskowe aspekty funkcjonowania przedsiębiorstwa - Hałasa, Jolanta Małgorzata; Rumianowska, Irena (Corporate Social Responsibility and ecological aspects function of firm, 2007)
The idea of corporate social responsibility assumes the company has obligations towards not only clients and owners but also towards other stakeholders. The conception of corporate social responsibility has three levels. The first is economic level, the second - social level, and third one is ecological level. The firm concentrates on different goals at each level. In practice, we can see many different models of social responsibility. For example, firms either take obligations to gain profit like in Friedman’s theory or take fuli obligations towards all stakeholders. A special kind of obligation is responsibility for environment. We can observe relations between Corporation and natural environment. There are many rational, useful activities under taken by firms.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1190, s. 535-547